Empowering Parents for the Golden Age: A Community-Based Parenting Education Initiative at Al-Fatah Kindergarten - Ferdinanda Sherly Noya; St. Adrianti; Nandalita Nunuela (DEVOTIONIS, 2025)
Early childhood, especially from birth to age six, is a foundational phase often described as the “golden age” of human development, when rapid brain growth and learning potential are at their peak. During this critical stage, parenting plays a pivotal role in shaping children's cognitive, emotional, social, and moral development. However, in many contexts, including in Indonesia, parents often face challenges due to a lack of parenting knowledge, limited access to educational resources, and socio-cultural barriers. In response to these challenges, this community service program was conducted at Al-Fatah Kindergarten in Ambon with the aim of enhancing parental understanding of early childhood development and increasing awareness of the significance of their role as primary educators. The program employed a two-day interactive workshop approach, featuring themes on parenting for Generation Alpha and holistic child development. The sessions were delivered through participatory methods, including lectures, focus group discussions, real-life case sharing, and direct consultation with parenting experts. Results showed increased parental awareness and understanding of their role in child development, particularly regarding the impact of parenting styles, screen time management, emotional support, and developmental stimulation. The initiative also fostered a stronger school–community relationship and positioned the kindergarten as a collaborative center for parenting education. The success of the program illustrates that school-based parenting education, when delivered in culturally sensitive and engaging formats, can effectively bridge knowledge gaps and support families in providing nurturing, responsive, and developmentally appropriate care for their children. The findings reinforce the need for sustainable, community-driven models of parenting education that empower parents as active contributors to lifelong learning and early childhood success.